Hubungan Pengetahuan Kesehatan Gigi dan Mulut Pasien Terhadap Kepatuhan Menjalani Perawatan Berulang - Isnia Maulidah; M Roelianto; Galih Sampoerno (Conservative Dentistry Journal, 2018)
Background: Dental caries is one of oral and dental disease that has high prevalence in Indonesia. The fact showed that there are many dental caries were in advanced condition, resulting in root canal treatment needed. The failure of root canal treatment usually caused by patient non compliance in multivisit treatment. It was probably because of the lack of public knowledge about oral and dental health. Purpose: This study was to investigate the correlation between oral and dental health knowledge with patient compliance in multivisit treatment. Methods: An analytic survey using cross sectional design was carry out on 35 patients in UPF Konservasi Gigi RSGMP FKG UNAIR around September-November 2011. The data gathering was done using both questionnaire and focused interview. The test of Spearman correlation was used to measure the correlation between the oral and dental health knowledge to patient compliance in multivisit treatment. Result: This study showed that there was no significant correlation between oral and dental health knowledge to patient compliance (p=0,837). But there was significant correlation between patient compliance with patient motivation  (p=0,006), needs (p=0,020), perception (p=0,018) and dental treatment cost (p=0,034) with patien compliance in multivisist dental treatment. Conclusion: There was no significant correlation between oral and dental health knowledge to patient compliance. There are other factors that give significance contribution to the increasement of complianced beside knowledge, such as motivation, needs, patient’s perception in continousy treatment and and cost.